Plasties of lateral duodenal defects with pedunculated jejunum patches - Criado, Francisco; Sorondo, Martín; Martinez, Jorge; Iriondo, Nilsa; Lizaso, Isabel (Cirugía del Uruguay, 1975)
Out of the different solutions proposed to repair the large defects of the duodenal wall , the authors carry out an experimental evaluation upon the use of pediculated jejunal patches. They utilized the technique on 8 dogs with almost circumferential defects of the 2nd part of the duodenum, from 7 to 9 centimeters in length. As a patch, they used an isolated jejünal loop, which had been opened by its antemesenteric border, trimmed in order to adapt it to the configuration of the opening, and utured in one plane. Results were uniformly good, both from the anatomical and functional standpoints, and the authors conclude that the procedure may be used on selected clinical cases.